Plasma Concentration of 12-Hydroxyeicosatetraenoic Acid, Single Nucleotide Polymorphisms of 12-Lipooxygenase Gene and Vaso-Occlusion in Sickle Cell Disease - Duru, Augustine Nwakuche; Ocheni, Sunday; Ibegbulam, Obike; Okpala, Iheanyi (Frontiers in Genome Editing, 2021)
Background and Novel Aspect of this Work: In the light of previous findings that inflammation predisposes to intercellular adhesion and microvascular occlusion in sickle cell disease (SCD), this study investigated the relationship between the number of vaso-occlusive events in SCD, plasma levels of the pro-inflammatory molecules 12-Hydroxyeicosatetraenoic acid (12-HETE), TNF-α and IL-1β; and single nucleotide polymorphisms (SNPs) in the gene 12-Lipooxygenase (ALOX-12), which encodes the enzyme 12-Lipoxygenase that catalyzes the biosynthesis of 12-HETE. Objective: To evaluate the relationship between vaso-occlusion in SCD and plasma concentrations of 12-HETE, TNF-α, and IL-1β; and single nucleotide polymorphisms (SNPs) in ALOX-12 gene. Participants and Methods: In 50 HbSS patients, the numbers of vaso-occlusive crisis requiring hospital treatment in the previous 1 year and the vaso-occlusive complications of SCD developed to date (e.g stroke) were added to obtain the vaso-occlusive events (VOE) score. In the HbSS patients and 30 healthy sibling control persons, plasma concentrations of 12-HETE, TNF-α and IL-1β were measured by ELISA, the ALOX12 SNPs rs2073438 and rs1126667 detected by DNA sequencing, and the accrued data statistically analyzed. Results: Compared to SCD patients with VOE score 0–1, those with scores ≥3 had higher plasma levels of 12-HETE (p < 0.0001) and TNF-α (p = 0.19), but not IL-1β (p = 0.27). VOE score showed strong direct correlation with plasma level of 12-HETE (r = 0.65, p < 0.0001), but not with TNF-α nor IL-1β. Neither VOE score nor plasma concentration of 12-HETE showed any relationship with the ALOX12 SNPs rs2073438 and rs1126667. Conclusion: The strong direct correlation of VOE score with plasma concentration of 12-HETE suggests that the clinical relevance of this pro-inflammatory molecule in SCD-associated vaso-occlusion needs to be evaluated in further studies.